Optimization of Double-Skin Façades for Heating and Cooling in High-Rise Buildings: A Case Study in Kuwait City - Ghaith, Fawaz Khaled; Buhamad, Mohammad Hamad (Journal of engineering sciences and information technology, 2024)
In hot arid climates such as Kuwait, the challenge of heat transfer through building façades has prompted significant debate. Determining the heating and cooling loads of buildings in such environments is crucial to assess their energy efficiency. Objectives: This research was undertaken to gauge the energy efficiency of high-rise buildings outfitted with double facades in Kuwait City, emphasizing their heating and cooling loads. Methods: A parametric computer simulation was employed, utilizing the eQUEST program, to model a prototype of a high-rise building with double facades in Kuwait City. This model was used to quantify the double façade’s efficacy in mitigating heating and cooling loads, drawing comparisons with typical glazing buildings in the city. Results: Findings indicate that the total energy consumption for space conditioning in buildings with DSFs was 235 MWh/year for heating and 2,890 MWh/year for cooling, aligning well with the energy conservation program (MEW/R-6/2014) benchmarks in Kuwait. Additionally, when optimally configured with materials like polycarbonate and an optimal cavity width of 50cm, DSFs contributed to a significant reduction in building loads. Specifically, the DSFs constituted 2,900 MWh/year of the total cooling load and 235 MWh/year of the heating load. Conclusion: Our results underscore the potential of double-skin façades in decreasing energy consumption for both heating and cooling purposes, demonstrating their superiority over conventional high-rise building facades in Kuwait City.